Cardiovascular Autonomic Nervous System Function and Aerobic Capacity in Type 1 Diabetes - Hägglund, Harriet; Uusitalo, Arja; Peltonen, Juha E.; Koponen, Anne S.; Aho, Jyrki; Tiinanen, Suvi; Seppänen, Tapio; Tulppo, Mikko; Tikkanen, Heikki O. (Frontiers in Physiology, 2012)
Impaired cardiovascular autonomic nervous system (ANS) function has been reported in type 1 diabetes patients. ANS function, evaluated by heart rate variability (HRV), systolic blood pressure variability (SBPV) and baroreflex sensitivity (BRS), has been linked to aerobic capacity (VO2peak) in healthy subjects, but relationship is unknown in type 1 diabetes. We examined cardiovascular ANS function at rest and during function tests, and its relations to VO2peak in type 1 diabetes individuals. Ten type 1 diabetes patients (T1D) (34 ± 7 years) and 11 healthy control (CON) (31 ± 6 years) age and leisure-time physical activity-matched men were studied. Autonomic nervous system function was recorded at rest and during active standing and handgrip. Determination of VO2peak was obtained with graded cycle ergometer test. During ANS recordings SBPV, BRS, and resting HRV did not differ between groups, but alpha1 responses to manoeuvres in detrended fluctuation analyses were smaller in T1D (active standing; 32%, handgrip; 20%, medians) than in CON (active standing; 71%, handgrip; 54%, p < 0.05). VO2peak was lower in T1D (36 ± 4 ml ∙ kg-1 ∙ min-1) than in CON (45 ± 9 ml ∙ kg-1 ∙ min-1, p < 0.05). Resting HRV measures, RMSSD, HF and SD1 correlated with VO2peak in CON (p < 0.05) and when analysing groups together. These results suggest that T1D had lower VO2peak, weaker HRV response to manoeuvres, but not impaired cardiovascular ANS function at rest compared with CON. Resting parasympathetic cardiac activity correlated with VO2peak in CON but not in T1D. Detrended fluctuation analysis could be a sensitive detector of changes in cardiac ANS function in type 1 diabetes.